Evaluation of a Sports-Based Positive Youth Development Program for First Nations Youth: Experiences of Community, Growth and Youth Engagement - Halsall, Tanya (Université d'Ottawa / University of Ottawa, 2016)
In contrast with mainstream Canadian youth, First Nations youth experience many health disparities. Researchers recommended that interventions designed to promote First Nations youth development use a strengths-based lens that recognizes contextual challenges. Furthermore, leadership programming for First Nations youth has begun to show promising outcomes. The overall purpose of this research was to examine the Youth Leadership Program (YLP) program to gain an understanding of program implementation and perceived outcomes related to both individual and community development. Two studies were conducted to fulfil the research purpose. The first study applied a qualitative approach that examined contextual dynamics, implementation issues (Article 1) and perceived impacts (Article 2). Data were collected using semi-structured interviews and analyzed using thematic analysis. Overall, 12 program staff (5 females), one Elder (male) and 10 youth (8 females) participated in semi-structured interviews. In addition, 11 youth (7 females) participated in two focus groups. The data from the youth and staff were included in the first study. The focus group data was included in the second study. In Article 1, findings were categorized into strategies for success and challenges. The following six themes were identified within the strategies for success: (a) designing youth engagement strategies, (b) being creative and adaptable, (c) being a positive presence, (d) applying experiential learning techniques, (e) balancing the integration of culture with youth voice and (f) identifying partnerships and developing relationships with the community. The three themes relating to challenges were (a) community diversity, (b) social issues and (c) staff burn-out. In Article 2, data analysis resulted in three themes that describe the perceived program effects at the participant, staff and community levels. The three major themes include: a) progressive leadership development, b) enhanced relationships and c) increased community participation. Within the second study (Article 3), methods were based on youth participatory evaluation and Photovoice and the design included capacity building, stakeholder analysis, photo exploration and utilization-focused activities. Using a thematic analysis, five themes were identified: (a) fun and fulfilling to engage the children, (b) positive outcomes for youth leaders, (c) community impacts, (d) challenges and (e) opportunities for improvement. Findings for each study are discussed in relation to current theory and practice, and recommendations are provided for future research and programming. This research makes contributions to applied positive youth development programming, community-based research with First Nations youth, youth-led participatory research and developmental systems theory.